PRINCIPLES OF MODELING IN SOLVING PHYSICAL PROBLEMS (Scientific journal of the Fergana State University, 2023)
The article presents the study of physical processes, bringing them into mathematical form, creating and classifying models and methods of analysis and synthesis. The stages of solving practical tasks performed when applying mathematical modeling to solve a physical problem are proposed, the process of modeling devices made of semiconductor materials that underlie the development of modern technology is described.